Obtenção e caracterização de um eco-compósito à base de látex e bainha da palha do coqueiro para isolamento térmico e acústico - Souza Filho, José Ribeiro de (2015)
With the emergence of new technologies, has grown the need to use new materials, and this has intensified research on the collection and use of materials from renewable sources, is to reduce production costs and / or environmental impact. In this context, it was found that the sheath coconut straw, can be utilized as raw material for the production of a eco-composite that can be used as a thermal and acoustic insulator. After selected from the coconut sheaths were subjected to treatment with aqueous 2 % sodium hydroxide (NaOH). The composite study was produced with the sheath and coconut natural latex, with coconut sheath percentage in the proportions 15%, 25% and 35% of the total compound volume. Physical, thermal and acoustic properties of the composites were analyzed in order to obtain data on the use of viability as thermoacoustic insulation. The CP15 composites, CP25 and CP35 showed thermal conductivity 0.188 W/m.K, 0.155 W/m.K and 0.150 W/m.K, respectively. It can be applied as thermal insulation in hot systems to 200 ° C. The CP35 composite was more efficient as a thermal and acoustic insulation, providing 20% noise reduction, 31% and 34% for frequencies of 1 kHz, 2 kHz and 4 kHz, respectively. The analyzes were based on ABNT, ASTM, UL. Based on these results, it can be concluded that the eco-composite produced the hem of coconut can be used as thermal and acoustic insulation. Thus, it gives a more noble end to this material, which most often is burned or disposed of improperly in the environment.